Investment agreement in the Western Hemisphere : a compendium (OAS WashingtonUS, 1999)
Covers the key provisions of 58 bilateral investment treaties signed between countries of the region. Highlights the investment provisions included in the multilateral trade and integration arrangements found in the Western Hemisphere. Examines the investment provisions in the Bolivia-Mexico, Costa Rica-Mexico and Canada-Chile Free Trade Areas. Looks at the Chile-Mexico, Mexico-Nicaragua, and the Central America-Dominican Republic Free Trade Area.
DC